TEACHER DIFFICULTIES IN DEVELOPING LEARNING MODULES UNDER THE MERDEKA CURRICULUM: A MIXED-METHOD STUDY - Corin, Chey Cillie; Haryanto, Eddy; Yantoro, Yantoro (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to analyze the difficulties faced by elementary school teachers in developing learning modules under the merdeka curriculum for phase A at KKG Gugus Nusantara Muara Tembesi. The research employed a mixed-method approach with a sequential explanatory design, combining quantitative and qualitative data consecutively. Data were collected through questionnaires completed by 30 teachers and in-depth interviews with 10 teachers actively involved in module development. The results revealed three major areas of difficulty: conceptual understanding of the merdeka curriculum philosophy and the linkage between Learning Outcomes (CP) and Learning Progressions (ATP), technical limitations in designing authentic assessments and differentiated instruction, and a lack of collaborative support within the teachers’ working group (KKG). The study concludes that strengthening teacher capacity requires collaborative and reflective approaches through professional learning communities. It recommends developing a sustainable mentoring model to enhance pedagogical competence and the effectiveness of merdeka curriculum implementation in primary schools.